Settling down in Southwest Asia: the Epipalaeolithic-Neolithic transformation - Watkins, Trevor (Frontiers in Human Dynamics, 2023)
Permanent settlement began in southwest Asia across the end of the Pleistocene (the Epipalaeolithic) and the beginning of the Holocene (the Neolithic). Aggregation represents a transformation of the cultural niche, involving major social and cultural innovations and profound developments of the strategies of subsistence. At first, the scalar stress of living in large, permanent communities was diffused through corporate effort in the construction and maintenance of monumental communal buildings, a complex material symbolism, and increasing intensity of communal rituals; participation demonstrated commitment and conformity to community norms. As cultivated crops and managed herds of sheep and goat gradually became the predominant source of subsistence, the old sharing ethos was overtaken by the household as the central socio-economic unit; the household became the focus for ritual and symbolism. As population aggregations grew larger, their supra-regional networks of socio-economic sharing and exchange also became more complex, extensive and intensive. The new cultural niche based on networked aggregations produced a marked acceleration in both the rate of cultural accumulation and the rate of demographic growth. At the end of the Neolithic, plough-agriculture began in place of horticulture; there are the first signs of mixed agropastoral economies, the marking of private property, new technologies (ceramics and copper metallurgy), and, in southern Iraq, irrigation agriculture. At this time, too, the accelerating expansion of the population of farmers is marked by the appearance of their new settlements in all directions.